Hardwiring microbes via direct interspecies electron transfer: mechanisms and applications. Issue 8 (28th June 2016) - Cheng, Qiwen; Call, Douglas F.
Abstract : Direct interspecies electron transfer (DIET) has important implications for the design and operation of biological treatment processes. Abstract : Multicellular microbial communities are important catalysts in engineered systems designed to treat wastewater, remediate contaminated sediments, and produce energy from biomass. Understanding the interspecies interactions within them is therefore essential to design effective processes. The flow of electrons within these communities is especially important in the determination of reaction possibilities (thermodynamics) and rates (kinetics). Conventional models of electron transfer incorporate the diffusion of metabolites generated by one organism and consumed by a second, frequently referred to as mediated interspecies electron transfer (MIET). Evidence has emerged in the last decade that another method, called direct interspecies electron transfer (DIET), may occur between organisms or in conjunction with electrically conductive materials. Recent research has suggested that DIET can be stimulated in engineered systems to improve desired treatment goals and energy recovery in systems such as anaerobic digesters and microbial electrochemical technologies. In this review, we summarize the latest understanding of DIET mechanisms, the associated microorganisms, and the underlying thermodynamics. We also critically examine approaches to stimulate DIET in engineered systems and assess their effectiveness. We find that in most cases attempts to promote DIET in mixed culture systems do not yield the improvements expected based on defined culture studies. Uncertainties of other processes that may be co-occurring in real systems, such as contaminant sorption and biofilm promotion, need to be further investigated. We conclude by identifying areas of future research related to DIET and its application in biological treatment processes.